An All Solid-State Creatinine Biosensor Based on Ammonium-Selective PVC-NH2 Membrane Electrode - Cubuk, Osman; Altikatoglu, Melda; Erci, Vildan; Isildak, Ibrahim; Tinkilic, Nihat (AMER SCIENTIFIC PUBLISHERS, 2013)
An all solid-state polymeric membrane potentiometric biosensor has been developed for creatinine. The biosensor was based on all solid-state ammonium-selective electrode. The ammonium-selective electrode was prepared by using aminated poly(vinylchloride) together with nonaction and di-cyclohexyl-18-crown-6 as ionic conductivity enhancer. The ammonium-selective electrode exhibited almost a 52 +/- 5 mV slope between 1 x 10(-1) and 8 x 10(-6) M concentration levels of ammonium. Creatininase was immobilized on the surface of the polymeric all solid-state ammonium ion-selective electrode using a simple one step glutaraldehyde covalent attachment method. Potentiometric characteristics of the biosensor were examined in phosphate (pH 6.00, 7.20 and 8.20), Tris-HCl buffer (pH 6.00, 7.20 and 8.20) buffer and physiological model solutions at different creatinine concentrations (1.0 x 10(-1)-1.0 x 10(-6) M). The linear working range and sensitivity of the biosensor were also determined. The creatinine biosensor is highly sensitive and stable in both buffer solutions. Under obtimized conditions, the bioensor showed a linear response between 1 x 10(-1)-8 x 10(-5) M creatinine in both buffers at pH 7.20.
Keywords: Creatinine; All Solid-State Biosensors; Enzyme Sensors; Potentiometry; Creatininase; POTENTIOMETRIC BIOSENSORS; LIQUID-CHROMATOGRAPHY; UREA; SENSOR; SERUM; INJECTION; SYSTEM; POLYMER; SAMPLES; ISFET; Chemistry; Electrochemistry; Instruments & Instrumentation; Physics